Oberpleistozäne paläoklimatische Veränderungen im Zentral-Sinai (Ägypten) - Rögner, Konrad; Smykatz-Kloss, Werner; Zöller, Ludwig (ERDKUNDE, 1999)
The present study continues previous research concerning the distribution and genesis of loess-like dissected sediments in the Central Sinai which had filled the wadis Firan and Esh Sheikh to a depth of 55 m. New results for the paleoclimatic interpretation and the chronostratigraphy of these sediments are presented. Several approaches lead to the conclusion that the formation of the sediments occurred under climatic conditions different from the present-day hyper-arid climate of the area. Phases of more or less intensive initial soil formation are witnessed by macroscopically detectable accumulations of organic matter and fossilised root horizons. These reflect at least temporarily moister conditions. This statement is supported by intense carbonate solution and precipitation as well as by regularly occurring unconformities at the boundaries between fine-grained allochthonous layers and overlying coarser-grained layers rich in local crystalline components. By means of TL dating a chronometric framework for the formation of the sediments could be established for the first time. It spans the entire marine isotope stage 2 (ca. 27–11 ka). Human activity during the youngest phase of sediment formation is proved by silex artefacts which apparently are reported for the first time from the area.